Analisis Implementasi Anggaran Berbasis Kinerja Pada Biro Kesejahteraan Rakyat Dikantor Gubernur Sumatera Utara - Mardiah Khofifah Hasibuan; Juliana Nasution (LPPM Universitas Labuhanbatu, 2021)
The purpose of this study was to examine the implementation of performance-based budgeting at the People's Welfare Bureau at the North Sumatra Governor's Office. Is the application in accordance with Permendagri No. 13 of 2006? The collection of data and information needed in research is carried out by field research. The data used are primary data obtained directly by interview, and secondary data through documentation. The results show that the implementation of performance-based budgeting at the people's welfare bureau at the North Sumatra governor's office has been running well according to the mandate of Permendagri No. 13 of 2006. The implementation of a performance-based budget system in the Regional Revenue and Expenditure Budget for the 2018-2021 Fiscal Year in North Sumatra Province is good, seen from the performance-based budget system which refers to the Minister of Home Affairs Regulation Number 13 of 2006 and the Minister of Home Affairs Regulation Number 37 year 2014.